Economics of Palm Oil Empty Fruit Bunches Bio Briquettes in Indonesia - Maitah, Mansoor; ProchÃ¡zka, Petr; Pachmann, Ales; Å rÃ©dl, Karel; Å˜ezbovÃ¡, Helena (International Journal of Energy Economics and Policy, 2016)
This study provides background data and justification for the development of bio briquettes from palm oil empty fruit bunches (EFB) and evaluates a pilot project utilizing this palm oil industry waste by-product in Indonesia. This activity is also important from the environmental standpoint since it helps in achievement of sustainable environment in Indonesia. This is due to the fact that EFB that is left to decay and is not processed is a significant source of pollution (Chiew and Shimada, 2013). Indonesia has become the world’s biggest palm oil producer with more than 20 million tons crude palm oil (CPO). Annual growth rate is about of 10%. This helped to Indonesian economic growth and poverty alleviation, provided benefits for big companies and thousands of smallholders. But this led also to deforestation and reduction of biodiversity. The Indonesian palm oil industry now still did not recover from palm oil prices drop down and use of palm oil by products should be on the focus also to support this Indonesian main business. Palm oil is facing criticism for using food crop as fuels, but EFB is absolutely non-food palm oil production by product. This by-product is underestimated in economic way and relatively huge amount is not used in Indonesia and could potentially contribute to sustainable green energy production especially for power generation needs In Indonesia. (Mohammed et al., 2012) Keywords: Sustainable development, Crude Palm Oil, Briquettes, Renewable Energy, Profitability JEL Classifications: Q2; Q4, Q5